A Survey Based Study for the Assessment of Knowledge and Practice of Community Pharmacy Personnel on Good Pharmacy Practice in Hyderabad, India. - Jagarlamudi, Anup; Begum, Asma; Teegala, Mahalakshmi (Indian Journal of Pharmacy Practice)
It has been more than two decades since the Good pharmacy practice guidelines were framed by WHO-FIP jointly and also The IPA had also framed the Good pharmacy practice guidelines 16 years back. The main objective behind the guidelines was to improve the quality of services provided by the community pharmacists and also to promote that the health of the patient is also the responsibility of these pharmacists. Nowadays the focus is on patient-centered Medication therapy and hence in our study we have tried to assess the knowledge and practice of community pharmacy personnel toward Good pharmacy practice guidelines in Hyderabad. We have developed a survey form consisting of 44 questions based on the WHO-FIP guidelines and also on the basis of IPA guidelines. A total of 500 survey forms were distributed at various community pharmacies covering all the areas of Hyderabad. We have received 302 filled in survey forms and these were analyzed question wise and the results obtained were disappointing. 43.3% of dispensing pharmacists were from a different educational background and 15.8% personnel were holders of 10+2 certificate and 3.97% were holders of 10th class certificate. The maximum number of days of training received were 180 days and the minimum number of days of training received were 0 days. Majority of dispensing pharmacists were aware of medication errors and when questioned about the action taken by them if they encountered a prescription with medication errors, surprisingly all of them answered that they will overlook such errors and again when asked why they were overlooking these errors, they have answered that they cannot question the doctors. The authorities must be extra vigilant while licensing a pharmacy and also should be inspecting these pharmacies frequently and also more educational reforms must be inculcated both at the institutional level and also at the practicing level. The practicing pharmacists must be encouraged to attend continuous educational and knowledge upgrading programmes.
Keywords: Community pharmacists; Dispensing pharmacists; Hyderabad; Good pharmacy Practice.